1993
DOI: 10.1073/pnas.90.16.7706
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal coiled-coil domain of beta is essential for gamma association: a model for G-protein beta gamma subunit interaction.

Abstract: We have identified the N terminus of the ,B subunit as an essential domain for G-protein Py assembly. A C-terminal fragment, P,-(130-340), fails to bind y unless coexpressed with the complementary N-terminal fragment, (17) and fos and jun (18).In the present paper, we propose a model for,Py interaction in which the subunits dimerize to form an a-helical coiledThe publication costs of this article were defrayed in part by page charge payment. This article must therefore be hereby marked "advertisement" (residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 38 publications
3
50
0
Order By: Relevance
“…Some WD-40 proteins, like RACK1, are made up entirely of WDrepeats IRon et al 1994). Others, including AN11, contain amino-terminal and carboxy-terminal extensions of various lengths, which may contribute to the regulatory function, as shown for the Gq3 subunit and the phospholipase A2 activating protein (Clark et al 1991;Garritsen et al 1993). Apart from the relatively loose WD-repeat consensus sequence, no significant sequence homology has been found between AN11 and any other identified WD-repeat protein, indicating that AN11 is a new member of this rapidly expanding family of proteins.…”
Section: Discussionmentioning
confidence: 98%
“…Some WD-40 proteins, like RACK1, are made up entirely of WDrepeats IRon et al 1994). Others, including AN11, contain amino-terminal and carboxy-terminal extensions of various lengths, which may contribute to the regulatory function, as shown for the Gq3 subunit and the phospholipase A2 activating protein (Clark et al 1991;Garritsen et al 1993). Apart from the relatively loose WD-repeat consensus sequence, no significant sequence homology has been found between AN11 and any other identified WD-repeat protein, indicating that AN11 is a new member of this rapidly expanding family of proteins.…”
Section: Discussionmentioning
confidence: 98%
“…1D demonstrates that both chimeras are capable of activating PI-PLC-f32 very well when expressed with y2. To address the possibility that the chimeras can interact with yl but cannot activate PI-PLC-f32, we tested for the direct interaction of the chimeras with yl by measuring the translocation of Gf3 subunits from the membrane fraction to the cytosol, based on the finding that in transfected cells, ylC71L, a Gyl that cannot be isoprenylated, will shift GP3 subunits that it can dimerize with from the membrane fraction to the cytosol (28,35). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Computer-assisted molecular modeling of the j3 and y subunits revealed that their N-terminal regions can form a-helical coiled-coil structures and it was postulated that 13 and y dimerize through these regions (34,35). However, the N-terminal coiled-coil structure cannot account, by itself, for the exceptional stability of f3y dimers (36).…”
mentioning
confidence: 99%
“…This question might be answered by understanding the proposed roles of Gg-or Gb-subunits in G-protein signaling. In general, G-protein g-subunits are found to play the following roles: (1) transducing signals by forming a heterodimer with Gb (Whiteway et al 1989;Garritsen et al 1993), (2) promoting G-protein activation by binding and modulating efficiency of receptor-G-protein coupling (Lambright et al 1994;Yasudaet al 1996;Rondard et al 2001;Chinault and Blumer 2003), (3) granting selective and discrete coupling of GPCRs with Gb (Kisselev et al 1995(Kisselev et al , 1999, and (4) promoting activation of the Gbg-effectors that cocluster with receptors (Chinault and Blumer 2003). Similarly, Gb-subunits were found to play an important role in providing a GPCR binding site for the G protein, which is critical for G-protein activation (Taylor et al Figure 6.-Deletion of gpgA cannot bypass the need for fluG in conidiation.…”
Section: Discussionmentioning
confidence: 99%